Thermally conductive composition
The thermally conductive composition, featuring a silicone-based resin with thermally conductive fillers, addresses the challenges of high thermal conductivity and reduced load on IC chips, while accommodating varying shapes, achieving effective heat dissipation and preventing load-induced damage.
Patent Information
- Application Number
- JP2024216506
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-03-29
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
AI Technical Summary
Thermally conductive sheets used in heat dissipation for IC chips face challenges in achieving high thermal conductivity while maintaining a suitable hardness to avoid excessive compressive loads on the IC chips, and in accommodating the varying shapes of multiple heat generating members.
A sheet-like thermally conductive composition is developed, comprising a resin composition with silicone and thermally conductive fillers, which exhibits high thermal conductivity, is easily deformable to follow the shape of heat generating members, and reduces the load applied to these members.
The thermally conductive composition achieves high thermal conductivity (22.8 W/mK or more) while maintaining a low compressive load, allowing it to effectively dissipate heat from IC chips and adapt to the shapes of multiple heat generating members, thus preventing damage from excessive loads.
Smart Images

Figure 2025038048000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermally conductive composition. This application claims priority to Japanese Application No. 2023-053524, filed on March 29, 2023, and incorporates by reference all of the contents of said Japanese application. [Background technology]
[0002] A heat dissipation member such as a heat sink is usually attached to a heat generating member such as an IC chip via a thermal interface material (TIM). Heat generated in the heat generating member is conducted to the heat dissipation member via the thermal interface material.
[0003] As the above-mentioned thermally conductive material, for example, a thermally conductive sheet in which spherical alumina and carbon fibers are blended as thermally conductive filler in a resin matrix has been proposed (see Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2019 / 244890 [Patent Document 2] JP 2014-31501 A Summary of the Invention [Problem to be solved by the invention]
[0005] A thermally conductive sheet is a component that is required to have excellent thermal conductivity, and the thermal conductivity can be increased by increasing the amount of thermally conductive filler blended in. On the other hand, if the thermally conductive sheet contains an increased amount of thermally conductive filler, the sheet becomes hard. Thermally conductive sheets used for IC chips are attached to the IC chips while a certain compressive load is applied. Furthermore, the harder the thermally conductive sheet is, the greater the compressive load that needs to be applied when attaching the thermally conductive sheet to the IC chip needs to be.
[0006] Therefore, when attaching a hard thermally conductive sheet having high thermal conductivity to an IC chip, it is necessary to apply a relatively large compressive load. On the other hand, a large compressive load places a large load on the IC chip. If the compressive load applied during installation is maintained afterwards, the load will continue to be applied to the IC chip. Continuous application of a large load to the IC chip can cause the IC chip to fail.
[0007] In addition, a thermally conductive sheet may be attached so as to simultaneously cover multiple heat-generating components such as IC chips. In this case, since the shapes of the heat-generating components are usually not the same, the thermally conductive sheet is required to be able to deform in accordance with the different shapes of the heat-generating components. [Means for solving the problem]
[0008] Under these circumstances, the inventors of the present invention conducted extensive research and completed a thermally conductive composition that has excellent thermal conductivity, is easily conformable to the shape of heat-generating components such as IC chips, and reduces the load on the heat-generating components.
[0009] A thermally conductive composition according to one embodiment of the present invention is a sheet-shaped thermally conductive composition comprising a resin composition containing silicone and a thermally conductive filler, When compressed by 50%, the initial compression load was 1.0N / mm 2 The ratio of the compressive load value after 1 minute to the initial compressive load value is 0.5 or less, The apparent thermal conductivity when compressed and deformed by 20% is 22.8 W / mK or more. Effect of the Invention
[0010] The thermally conductive composition according to one embodiment of the present invention has high thermal conductivity. The thermally conductive composition is easily deformed so as to conform to the shape of a heat generating component such as an IC chip. When the thermally conductive composition is attached to a heat-generating component such as an IC chip, the load applied to the IC chip or the like can be reduced. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a cross-sectional view that illustrates an IC chip to which a heat sink is attached via a sheet-shaped thermally conductive composition according to an embodiment of the present invention. [Diagram 2] Fig. 2A is a perspective view showing an example of a sheet-shaped thermally conductive composition according to an embodiment of the present invention, and Fig. 2B is a partially enlarged view of a cross section taken along line AA in Fig. 2A. [Diagram 3] FIG. 3 is a schematic cross-sectional view of the tip portion of an extruder and a T-die used in the production of a sheet-shaped thermally conductive composition according to this embodiment. [Figure 4] 4A to 4D are diagrams illustrating another example of the method for producing a sheet-shaped thermally conductive composition according to an embodiment of the present invention. [Diagram 5] 5A to 5C are diagrams illustrating a method for evaluating the tracking ability in the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The outline of the embodiments of the present invention will be described below. (1) A sheet-shaped thermally conductive composition comprising a resin composition containing silicone and a thermally conductive filler, When compressed by 50%, the initial compression load was 1.0N / mm 2 The ratio of the compressive load value after 1 minute to the initial compressive load value is 0.5 or less, A thermally conductive composition having an apparent thermal conductivity of 22.8 W / mK or more when compressed and deformed by 20%.
[0013] This sheet-shaped thermally conductive composition has high thermal conductivity and can reduce the load on the heat-generating component after installation. In addition, it easily conforms to the shape of the heat-generating component when installed. Furthermore, even if the heat-generating component is deformed by heat after installation, it can conform to the deformation.
[0014] (2) In the thermally conductive composition of (1) above, the compressive load value after one minute is 0.4 N / mm 2 It is preferable that: In this case, it is possible to prevent a high load from being continuously applied to the IC chip after attachment.
[0015] (3) In the thermally conductive composition of (1) or (2) above, the resin composition preferably contains polydimethylsiloxane as the silicone. (4) In any of the thermally conductive compositions (1) to (3) above, the resin composition preferably contains, as the thermally conductive filler, an anisotropic thermally conductive filler and a non-anisotropic thermally conductive filler. (5) In any of the thermally conductive compositions (1) to (4) above, the resin composition preferably contains, as the thermally conductive filler, a fibrous filler, a scaly filler, and a spherical filler.
[0016] These resin compositions are suitable as resin compositions for forming thermally conductive sheets that have high thermal conductivity and can reduce the load on IC chips.
[0017] (6) In the thermally conductive compositions of (1) to (5) above, the resin composition preferably contains carbon fibers, scaly graphite powder, and spherical zinc oxide particles as the thermally conductive filler. When zinc oxide particles are contained as a thermally conductive filler, the thermal conductivity of the sheet-shaped thermally conductive composition is easier to increase than when alumina particles are contained. When carbon fiber and flake graphite powder are used in combination as a thermally conductive filler, it is easier to increase the thermal conductivity while reducing the initial load of the sheet-like thermally conductive composition compared to when only one of carbon fiber and flake graphite powder is contained.
[0018] (7) In the thermally conductive composition (6) above, the total content of the carbon fibers, the scaly graphite powder, and the spherical zinc oxide particles is preferably 50% by volume or more and 70% by volume or less. (8) In the thermally conductive composition of (6) or (7) above, the content of the carbon fibers is preferably 30% by volume or more and 45% by volume or less. These cases are more suitable for ensuring good thermal conductivity while suppressing the compressive load value required for 50% compressive deformation.
[0019] Hereinafter, a sheet-shaped thermally conductive composition according to an embodiment of the present invention will be described in detail, but the embodiment of the present invention is not limited to the following embodiment.
[0020] In an embodiment of the present invention, the "sheet-shaped thermally conductive composition" includes both a block-shaped product obtained after molding by extrusion molding or the like, and cut products (including sliced sheet-shaped products) obtained by appropriately cutting the block-shaped product. Here, an embodiment of the sheet-shaped thermally conductive composition will be described using a sliced sheet as an example.
[0021] The sheet-shaped thermally conductive composition according to the present embodiment is a member provided between an IC chip and a heat sink. The thermally conductive composition is made of a resin composition containing silicone and a thermally conductive filler. Here, silicone is a polymer compound having a main skeleton formed by siloxane bonds. Fig. 1 is a cross-sectional view showing an IC chip to which a heat sink is attached via a sheet-shaped thermally conductive composition according to an embodiment of the present invention. Fig. 2A is a perspective view showing an example of a sheet-shaped thermally conductive composition according to an embodiment of the present invention. Fig. 2B is a partially enlarged view of the cross section taken along line AA in Fig. 2A. It should be noted that all of the drawings in this application are schematic diagrams and do not accurately reflect the actual dimensions of each component.
[0022] A sheet-like thermally conductive composition 1 (hereinafter also referred to as a thermally conductive sheet 1) is disposed between an IC chip 11 and a heat sink 12, as shown in Fig. 1. The thermally conductive sheet 1 is used with one surface in contact with the IC chip 11 and the other surface in contact with the heat sink 12. In this way, the heat sink 12 is attached to the IC chip 11 via the thermally conductive sheet 1. Therefore, the heat generated by the IC chip 11 is dissipated by the heat sink 12 to the outside of a housing (not shown).
[0023] 1 shows a usage mode of a thermally conductive sheet 1 attached to the upper surface of one IC chip 11. Meanwhile, a sheet-shaped thermally conductive composition (thermally conductive sheet) according to an embodiment of the present invention may be a thermally conductive sheet that is attached so as to simultaneously cover heat-generating components such as a plurality of IC chips.
[0024] When the thermally conductive sheet 1 was compressed by 50% in the thickness direction (the vertical direction in Figs. 2A and 2B), the initial compression load value was 1.0 N / mm 2 The following is the result. When attaching the thermally conductive sheet 1 to the IC chip 11, a predetermined load is applied to press the thermally conductive sheet 1 onto the IC chip 11. At this time, if the flexibility of the thermally conductive sheet 1 is insufficient, the thermally conductive sheet 1 and the IC chip 11 may not adhere to each other, and gaps may occur at the interface between them. Furthermore, when a single thermally conductive sheet 1 is attached to cover multiple heat-generating components at the same time, it may not be able to follow the shapes of all the heat-generating components, and gaps may occur between any of the heat-generating components.
[0025] On the other hand, if the load applied when attaching the thermally conductive sheet 1 is large, the thermally conductive sheet 1 and the IC chip 11 will be in close contact with each other and gaps will be less likely to occur, but in that case, there is a risk that the IC chip 11 will be damaged. In contrast, the initial compression load value is 1.0N / mm 2In many cases, the thermally conductive sheet 1 described below can be properly attached to an IC chip or the like within the range of the compression load allowance determined for each IC chip. In addition, if the initial compression load value is 1.0 N / mm 2 When the thermally conductive sheet 1 described below is attached so as to cover multiple heat generating components at the same time, it easily conforms to the shape of each of the heat generating components.
[0026] The initial compression load value is 0.7N / mm 2 It is preferable that the thickness is less than or equal to the thickness of the IC chip. This is more suitable for closely attaching the thermally conductive sheet to the IC chip without applying a load to the IC chip. In the thermal conductive sheet 1, the initial compression load value is usually 0.1 N / mm 2 Above, but 0.1N / mm 2 It may be smaller.
[0027] The thermally conductive sheet 1 has a ratio of a compressive load value after 1 minute has elapsed since it was compressed by 50% in the thickness direction (hereinafter referred to as a compressive load value after 1 minute) to the initial compressive load value of 0.5 or less. In this case, the thermally conductive sheet 1 is easily deformed according to the shape of the IC chip 11. Therefore, when attached to the IC chip 11, it can follow the shape of the IC chip 11. It is particularly suitable for attachment so as to cover multiple heat generating components at the same time. Furthermore, when the IC chip 11 is deformed by heat, the thermally conductive sheet 1 is easily deformed to follow the deformation. It is also possible to prevent the IC chip from being subjected to a continuous high load.
[0028] The compressive load value of the thermal conductive sheet 1 after one minute is 0.4 N / mm 2 It is preferable that: In this case, the thermally conductive sheet 1 is attached to the IC chip 11 with a predetermined load applied thereto, and then the load is sufficiently released. Therefore, it is possible to prevent the IC chip 11 from being subjected to a large load for a long period of time.
[0029] The compression load value after 1 minute is 0.2N / mm 2More preferably, it is 0.15 N / mm 2 It is particularly preferred that: There is no lower limit to the compressive load value after 1 minute has elapsed, and it may be any value that allows the thermally conductive composition to maintain its sheet-like shape.
[0030] The initial compression load value when the thermally conductive sheet 1 is compressed and deformed by 50% in the thickness direction is measured using a universal testing machine (e.g., Instron 5969 (manufactured by Instron)) as a measuring device, compressing the thermally conductive sheet 1 in the thickness direction to a thickness of "thickness before measurement x 0.5" at a compression speed of 5 mm / min, and measuring the load value at that time. Furthermore, based on the obtained measurement value, the load value per unit area (mm 2 ) and calculate the compression load value per unit. In addition, the measurement of the compressive load value after one minute is performed is performed in the state where the initial compressive load value was measured (a state where the specimen is compressed by 50% in the thickness direction) and the load value is measured after one minute. Furthermore, the unit area (mm 2 ) and calculate the compression load value per unit.
[0031] The thermally conductive sheet 1 has an apparent thermal conductivity of 22.8 W / mK or more when compressed and deformed by 20% in the thickness direction. If the apparent thermal conductivity is less than 22.8 W / mK, the thermal conductivity is insufficient. The aforementioned apparent thermal conductivity of the thermally conductive sheet 1 is preferably 26.6 W / mK or more.
[0032] The apparent thermal conductivity of the thermal conductive sheet 1 is calculated by compressing the sheet to a thickness of "thickness before measurement x 0.8" (20% compression) and measuring the thermal resistance (Kcm 2 / W) and the thickness (cm) of the thermally conductive sheet at the time of measurement, according to the following formula (1).
[0033] Apparent thermal conductivity (W / mK) = thickness of thermal conductive sheet at time of measurement (cm) ÷ thermal resistance value when compressed and deformed by 20% (Kcm 2 / W) × 100 (1)
[0034] The thermal resistance value when compressed and deformed by 20% is measured using a thermal conductivity measuring device (for example, TIMtester1400 (manufactured by AnalysisTech)) with the thermal conductive sheet 1 compressed and deformed by 20%.
[0035] The thickness of the thermally conductive sheet 1 is not particularly limited, but is, for example, 0.05 mm or more and 3.0 mm or less. In this case, the thermally conductive sheet 1 can be suitably used as a member that efficiently transfers heat between the IC chip 11 and the heat sink 12. The thickness of the thermally conductive sheet 1 is preferably 0.05 mm or more and 2.5 mm or less. This allows for better heat dissipation performance while ensuring conformability to the shapes of the IC chip 11 and the heat sink 12. On the other hand, if the thickness of the thermally conductive sheet 1 is less than 0.05 mm, it may not be possible to fully conform to the shapes of the IC chip 11 and the heat sink 12. Also, if the thickness exceeds 2.5 mm, the heat dissipation performance may be poor due to the thermal resistance of the sheet itself.
[0036] The thermally conductive sheet 1 has, for example, a rectangular shape in plan view. In this case, the vertical and horizontal dimensions of the thermally conductive sheet 1 may be determined taking into consideration the dimensions of the member to which the thermally conductive sheet 1 is attached, such as the IC chip 11, and for example, both the vertical and horizontal dimensions are independently 10 mm or more and 120 mm or less. The planar shape of the thermal conductive sheet 1 is not limited to a rectangle, and may be a shape other than a rectangle, such as a circle or an ellipse. In the case of a circle, the diameter is, for example, 10 mm or more and 120 mm or less. In the case of an ellipse, the major axis or minor axis is, for example, 10 mm or more and 120 mm or less.
[0037] As shown in FIG. 2B, the thermally conductive sheet 1 contains a matrix component 2 and a thermally conductive filler 4. In the thermally conductive sheet 1, all components other than the thermally conductive filler are collectively referred to as matrix components. In the thermally conductive sheet 1, weld lines may be formed in the thickness direction.
[0038] The matrix component 2 contains silicone, and therefore the thermally conductive sheet 1 has excellent heat resistance. In this embodiment, the silicone may contain a cross-linked product of silicone (hereinafter also referred to as cross-linked silicone), but from the viewpoint of easily ensuring good flexibility, it is preferable that the main component is uncross-linked silicone. Here, containing uncrosslinked silicone as a main component means that the proportion of uncrosslinked silicone in the total silicone is 50 mass % or more. The silicone may be composed solely of uncrosslinked silicone. By using uncrosslinked silicone as the main component, it becomes easier to release the load after attachment to an IC chip, etc.
[0039] As the uncrosslinked silicone, polydimethylsiloxane, which is a silicone in which all side chains are methyl groups and which does not contain unsaturated groups, is preferred. The silicone preferably contains 50% by mass or more of the polydimethylsiloxane, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more. The polydimethylsiloxane is a polymer that has low reactivity and excellent stability, so by increasing the proportion of the polydimethylsiloxane in the silicone, the flexibility of the thermally conductive sheet 1 can be improved.
[0040] The polydimethylsiloxane may be an oil or a millable type, but millable type polydimethylsiloxane is preferred, because it has good moldability when producing the thermally conductive sheet 1 by the method described below.
[0041] The molecular weight of the polydimethylsiloxane is preferably 60,000 or more and 700,000 or less in terms of mass average molecular weight MW. If the mass average molecular weight MW of the polydimethylsiloxane is less than 60,000, the polydimethylsiloxane tends to bleed out from the thermal conductive sheet 1. On the other hand, if the mass average molecular weight MW of the polydimethylsiloxane exceeds 700,000, the moldability and processability during production of the thermal conductive sheet 1 tend to be poor.
[0042] In the present disclosure, the mass average molecular weight MW of polydimethylsiloxane is the mass average molecular weight measured by gel permeation chromatography (GPC) using polystyrene as the standard substance in accordance with JIS-K7252-1:2008 “Plastics - Determination of average molecular weight and molecular weight distribution of polymers by size exclusion chromatography - Part 1: General rules”.
[0043] The kinetic viscosity of the polydimethylsiloxane is preferably 10,000 cps or more and 100,000 cps or less at 25° C. as measured with an Ubbelohde viscometer. If the kinetic viscosity is less than 10,000 cps, polydimethylsiloxane will easily bleed from the thermally conductive sheet 1. On the other hand, if the kinetic viscosity is more than 100,000 cps, the hardness of the thermally conductive sheet 1 will increase, and when placed between an IC chip and a heat sink, the thermally conductive sheet 1 may exhibit poor adhesion and conformability to the contact surfaces with the IC chip and the heat sink.
[0044] When the silicone contains a crosslinked silicone, the crosslinked silicone may be crosslinked by peroxide crosslinking or by addition reaction type crosslinking, but is preferably crosslinked by peroxide crosslinking, because crosslinked silicone crosslinked by peroxide crosslinking has better heat resistance. The crosslinked silicone may be, for example, a crosslinked silicone having a crosslinkable functional group such as a vinyl group in part of the side chain (including the terminal).
[0045] The silicone may contain silicone having a crosslinkable functional group such as a vinyl group in an uncrosslinked state.
[0046] The matrix component 2 may contain other elastomer components and the like to the extent that the required properties of the thermally conductive sheet 1 are not impaired.
[0047] The matrix component 2 may contain general additives such as a flame retardant, a reinforcing agent, a filler, a softener, a plasticizer, an antioxidant, a tackifier, an antistatic agent, a kneading adhesive, and a coupling agent. Examples of the flame retardant include magnesium hydroxide, aluminum hydroxide, platinum compounds, triazole compounds, iron oxides such as red iron oxide and black iron oxide, etc. These may be used alone or in combination of two or more kinds. The magnesium hydroxide can also function as a thermally conductive filler.
[0048] The matrix component 2 preferably contains a coupling agent such as a silane coupling agent as an additive. In particular, when zinc oxide particles are contained as the thermally conductive filler, it is preferable that the matrix component 2 contains a silane coupling agent. By using a combination of zinc oxide particles and a silane coupling agent, the flexibility of the thermally conductive sheet 1 can be increased.
[0049] Examples of the silane coupling agent include methyl trimethoxysilane, ethyl trimethoxysilane, propyl trimethoxysilane, butyl trimethoxysilane, pentyl trimethoxysilane, hexyl trimethoxysilane, hexyl triethoxysilane, octyl trimethoxysilane, octyl triethoxysilane, decyl trimethoxysilane, decyl triethoxysilane, dodecyl trimethoxysilane, dodecyl triethoxysilane, hexadecyl trimethoxysilane, hexadecyl triethoxysilane, octadecyl trimethoxysilane, octadecyl triethoxysilane, 3-methacryloxypropyl trimethoxysilane, 3-methacryloxypropyl triethoxysilane, etc. These may be used alone or in combination of two or more.
[0050] The thermally conductive sheet 1 contains a thermally conductive filler 4 . The thermally conductive filler 4 preferably contains an anisotropic thermally conductive filler (hereinafter also referred to as an anisotropic filler) and a non-anisotropic thermally conductive filler (hereinafter also referred to as a non-anisotropic filler). In this case, it is easy to ensure both high thermal conductivity and flexibility, and the moldability during production is also good. On the other hand, when the thermal conductive sheet 1 contains only anisotropic fillers, it is difficult to reduce the compression load value. Furthermore, cracks are likely to occur in the molded product during the manufacturing process. Moreover, when the thermal conductive sheet 1 contains only non-anisotropic fillers, it is difficult to increase the thermal conductivity of the thermal conductive sheet 1.
[0051] In the thermally conductive filler, an anisotropic filler refers to a filler having an aspect ratio of 2.0 or more, and a non-anisotropic filler refers to a filler having an aspect ratio of less than 2.0. The aspect ratio of the thermally conductive filler refers to the larger of the ratio of the major axis of the filler to the minor axis of the filler and the ratio of the major axis of the filler to the thickness of the filler. The above-mentioned major axis, minor axis, and thickness correspond to the length, width, and height, respectively, of the circumscribed rectangular solid of the filler.
[0052] The anisotropic filler includes fibrous filler, scaly filler, plate-like filler, thin flake filler, and the like. The aspect ratio of the anisotropic filler is preferably 5.0 or more. The non-anisotropic filler includes spherical fillers, irregular fillers, and the like.
[0053] The thermally conductive sheet 1 preferably contains, as the thermally conductive filler, a fibrous filler, a scaly filler, and a spherical filler. In this case, the thermally conductive sheet 1 is more likely to satisfy the above-mentioned predetermined compressive load characteristics and thermal resistance value.
[0054] In this case, the content of the fibrous filler is preferably greater than the content of the scaly filler and the content of the spherical filler. In this case, it is also easy to reduce the compressive load value while increasing the thermal conductivity. On the other hand, if the amount of scaly filler is greater than the amount of fibrous filler, it is difficult to suppress the compressive load value, and if the amount of spherical filler is greater than the amount of fibrous filler, it is difficult to increase the thermal conductivity.
[0055] The thermally conductive sheet 1 preferably contains, as the thermally conductive filler, carbon fibers 4C, scaly graphite powder 4G, and spherical zinc oxide particles 4Z. In this case, it is preferable that the thermally conductive sheet 1 has the carbon fibers 4C and the graphite powder 4G oriented substantially in the thickness direction of the thermally conductive sheet 1, and the zinc oxide particles 4Z dispersed throughout the thermally conductive sheet 1. The thermally conductive sheet 1 having such a configuration is particularly suitable for increasing the thermal conductivity while suppressing the initial load of the sheet-like thermally conductive composition.
[0056] The fiber length of the carbon fiber 4C is preferably 20 μm or more. If the fiber length is less than 20 μm, it may be difficult to form a heat conductive path, and the heat conductive sheet 1 may have poor heat conductivity. On the other hand, a preferable upper limit of the fiber length of carbon fiber 4C is 500 μm from the viewpoint of ease of filling the thermally conductive sheet with the carbon fiber. The fiber length of the carbon fiber 4C is more preferably 50 μm or more and 300 μm or less.
[0057] The fiber diameter of the carbon fiber 4C is preferably 5 μm or more. If the fiber diameter is less than 5 μm, a heat conduction path is difficult to form, and the heat conductivity of the heat conductive sheet 1 may be poor. From the viewpoint of processability when producing the thermally conductive sheet 1, a preferred upper limit of the fiber diameter of the carbon fiber 4C is 20 μm.
[0058] The fiber length of a fibrous filler such as carbon fiber refers to the arithmetic mean value of the length in the fiber direction determined using a microscopic image of the fibrous filler. The fiber diameter of a fibrous filler refers to the arithmetic mean value of the dimension in the radial direction determined using a microscopic image of the fibrous filler. The fiber length and fiber diameter are determined by obtaining a microscopic image of the fibrous filler, randomly selecting 20 fibrous fillers from the image, measuring the length in the fiber direction and the dimensions in the radial direction of the selected fibrous fillers, and then based on the measurement results.
[0059] As the carbon fiber 4C, one type of carbon fiber may be used, or two or more types of carbon fibers may be used. Carbon fibers with different thermal conductivities may be used in combination as the carbon fiber 4C. When carbon fibers with high thermal conductivity are used, the thermal conductivity increases, but the initial compression load value required for 50% compression deformation also tends to increase. Therefore, by using carbon fibers with different thermal conductivities in combination, it becomes easier to adjust the thermal conductivity and the initial compression load value of the thermal conductive sheet 1.
[0060] The graphite powder 4G is preferably in the form of a flake, which is suitable for orienting the graphite powder in the thickness direction of the thermally conductive sheet 1 to enhance the thermal conductivity in the thickness direction. The graphite powder 4G may contain graphite powder other than flake-like graphite powder. A combination of a flake-like graphite powder and a non-flake-like graphite powder may be used.
[0061] The particle size of the flake graphite powder 4G is preferably 5 μm or more and 50 μm or less. If the particle size of the flake graphite powder 4G is less than 5 μm, it is difficult to form a heat conduction path in the thermal conductive sheet 1. On the other hand, if the particle size of the flake graphite powder 4G exceeds 50 μm, it is difficult to pack densely. The particle size of the flake graphite powder 4G is preferably 10 μm or more and 30 μm or less.
[0062] The particle size of a scaly filler such as scaly graphite powder refers to the D50 (50% median diameter) of the maximum length in the plate surface direction determined using a microscope image for measuring the particle size of the scaly filler. The above particle size is determined by obtaining a microscopic image for measuring the particle size of the scaly filler, randomly selecting 20 scaly fillers from the image, measuring the maximum length of the selected scaly fillers in the plate surface direction, and then based on the measurement results.
[0063] The zinc oxide particles 4Z preferably have a spherical shape. In this case, it is easier to fill the thermal conductive sheet 1 with zinc oxide particles 4Z compared to other shapes, and the zinc oxide particles 4Z are less likely to damage components of the manufacturing equipment.
[0064] The particle size of the zinc oxide particles 4Z is preferably 0.1 μm or more and 10 μm or less. If the particle size of the zinc oxide particles 4Z is less than 0.1 μm, a heat conduction path is difficult to form. On the other hand, if the particle size of the zinc oxide particles 4Z exceeds 10 μm, the orientation of the carbon fibers 4C and the scaly graphite powder 4G is easily hindered. In addition, the zinc oxide particles 4Z are likely to damage the steel members of the manufacturing equipment.
[0065] In the embodiment of the present invention, the particle size of the thermally conductive filler other than the fibrous filler and the scaly filler refers to the value of the median diameter (d50) measured by a laser diffraction / scattering method.
[0066] When the thermally conductive filler 4 contains carbon fibers 4C, scaly graphite powder 4G, and spherical zinc oxide particles 4Z, the preferred content of the thermally conductive filler 4 in the thermally conductive sheet 1 is such that the total content of the carbon fibers 4C, scaly graphite powder 4G, and spherical zinc oxide particles 4Z is 50 volume % or more and 70 volume % or less. If the total content of the carbon fibers 4C, the scaly graphite powder 4G, and the spherical zinc oxide particles 4Z is less than 50% by volume, sufficient thermal conductivity may not be ensured. On the other hand, if the total content exceeds 70% by volume, the thermal conductive sheet 1 becomes too hard, and when attached to an IC chip, it may not be possible to properly attach it with an allowable compression load value. Also, during the slicing process, which is one of the manufacturing processes for the thermal conductive sheet 1, cracks may occur in the sheet during molding, making it impossible to maintain the sheet shape. In the thermally conductive sheet 1, the total content of the carbon fibers 4C, the scaly graphite powder 4G, and the spherical zinc oxide particles 4Z is preferably 55% by volume or more and 70% by volume or less, which is more suitable for achieving both good thermal conductivity and appropriate hardness.
[0067] The content of the carbon fibers 4C in the thermally conductive sheet 1 is preferably 30% by volume or more and 45% by volume or less, which is suitable for ensuring good thermal conductivity of the thermally conductive sheet 1. When the content of carbon fiber 4C in thermally conductive sheet 1 is 30 volume % or more and 45 volume % or less, the content of graphite powder 4G is preferably 5 volume % or more and 10 volume % or less. By setting the total content of the three types of thermally conductive fillers to between 50 volume % and 70 volume % and setting the content of carbon fiber 4C and flake graphite powder 4G within the above range, it is possible to reduce the ratio of the compressive load value after 1 minute to the initial compressive load value while maintaining good thermal conductivity.
[0068] The total content of the scaly graphite powder 4G and the spherical zinc oxide particles 4Z in the thermally conductive sheet 1 is preferably 20% by volume or more and 30% by volume or less. In this case, it is more suitable to lower the compressive load value required for 50% compressive deformation while maintaining good thermal conductivity. More preferably, it is from 25% by volume to 30% by volume.
[0069] In the thermally conductive sheet 1, an example of a particularly suitable configuration of the thermally conductive filler 4 is, for example, It contains carbon fiber 4C, flake graphite powder 4G, and spherical zinc oxide particles 4Z. The total content of the carbon fiber 4C, the scaly graphite powder 4G, and the spherical zinc oxide particles 4Z is 50% by volume or more and 70% by volume or less, The content of carbon fiber 4C is 30% by volume or more and 40% by volume or less, The content of the scaly graphite powder 4G is 5% by volume or more and 10% by volume or less, The total content of the scaly graphite powder 4G and the spherical zinc oxide particles 4Z is 25 volume % or more and 30 volume % or less.
[0070] Next, a method for producing the thermally conductive sheet 1 will be described. The thermally conductive sheet 1 can be produced, for example, by a first production method including the following steps (a) to (c). (a) preparing a silicone-based composition containing uncrosslinked silicone, carbon fiber, graphite powder, zinc oxide particles, and optional ingredients such as a flame retardant and a coupling agent; (b) molding the prepared silicone composition; and (c) A step of slicing the molded silicone composition into sheets.
[0071] First, step (a) of preparing a silicone-based composition is carried out. Here, for example, a silicone-based composition is prepared by kneading uncrosslinked silicone, thermally conductive filler (carbon fiber, graphite powder, and zinc oxide particles), and various additives added as necessary, using a two-roll mill. In this case, some or all of the components may be supplied in the form of a compound.
[0072] Next, the prepared silicone composition is molded in a step (b) and the molded product is sliced into sheets in a step (c). The silicone composition may be molded, for example, using an extruder. FIG. 3 is a schematic cross-sectional view of the tip portion of an extruder and a T-die used in the production of a thermally conductive sheet 1 according to an embodiment of the present invention. The silicone composition fed into the extruder 30 is stirred and kneaded by the screw 34 and introduced into a first gap 32 of a T-die along a flow path 31 .
[0073] The silicone composition stirred and kneaded in the extruder 30 is first squeezed in the vertical direction (thickness direction) by the first gap 32 into a thin strip. At this time, the anisotropic thermally conductive filler mixed in the silicone-based composition is oriented in the flow direction (extrusion direction) of the silicone-based composition. Therefore, in the thin resin sheet 40 molded by passing through the first gap 32, the anisotropic thermally conductive filler is oriented in the plane direction of the resin sheet 40. In this embodiment, for example, carbon fibers or flake graphite powder corresponds to the anisotropic thermally conductive filler.
[0074] When the thin resin sheet 40 in which the thermally conductive filler is oriented passes completely through the first gap 32, the flow direction of the sheet, which was limited to the extrusion direction, is released and the flow direction changes to a direction approximately perpendicular to the extrusion direction. The resin sheet 40, whose flow direction has changed to a direction approximately perpendicular to the extrusion direction, passes completely through the first gap 32, and is then further extruded toward the second gap 33. As a result, the resin sheet 40, now approximately perpendicular to the extrusion direction, is folded and stacked in the second gap 33. At this time, most of the anisotropic thermally conductive filler (carbon fiber and flake-like graphite powder) is oriented in the plane direction of the resin sheet 40, so that the anisotropic thermally conductive filler in the resin sheet 40 stacked in the second gap 33 is oriented along the thickness direction (the vertical direction in FIG. 3).
[0075] Thus, in step (b), the silicone-based composition is extruded to form a resin sheet 40 in which the anisotropic thermally conductive filler is oriented in the extrusion direction, and then this resin sheet 40 is folded and laminated to produce a block.
[0076] Then, proceeding to step (c), the block in which the thin resin sheets 40 are laminated is sliced in a direction perpendicular to the thickness direction, resulting in a thermally conductive sheet 1 having a predetermined thickness and in which the anisotropic thermally conductive filler is substantially oriented in the thickness direction. The block of resin sheet 40 produced in step (b) itself can also be used as the sheet-like thermally conductive sheet according to an embodiment of the present invention.
[0077] In the T-die, the depths of the first gap 32 and the second gap 33 (i.e., the dimensions of the first gap 32 and the second gap 33 in the direction perpendicular to the paper surface in FIG. 3) are substantially uniform throughout the T-die. The depths of the first gap and the second gap are not particularly limited, and various design changes are possible depending on the product width of the thermally conductive sheet 1 to be manufactured.
[0078] The method for producing the thermally conductive sheet 1 is not limited to the first production method described above, and may be, for example, a second production method in which the following steps (d) to (f) are carried out. 4A to 4D are diagrams illustrating the second manufacturing method.
[0079] (d) preparing a silicone-based composition containing uncrosslinked silicone, carbon fiber, graphite powder, zinc oxide particles, and optional ingredients such as a flame retardant and a coupling agent; (e) molding the prepared silicone composition; and (f) slicing the molded silicone composition into sheets;
[0080] First, step (d) of preparing a silicone-based composition is carried out. Here, for example, uncrosslinked silicone, thermally conductive filler (carbon fiber, graphite powder, and zinc oxide particles), and further various additives added as necessary are kneaded with two rolls 51. After that, a sheet is formed to prepare a resin sheet 50 (see FIG. 4A). In this case, some or all of the components may be supplied in the form of a compound.
[0081] Next, step (e) is carried out to mold the silicone composition. In this step (e), the resin sheets 50 made of a silicone-based composition are folded and laminated so that the resin sheets 50 are in close contact with each other (see FIG. 4A). For example, by continuously supplying the resin sheets 50 onto a table 53 that repeats a periodic reciprocating motion, a laminate in which the resin sheets 50 are laminated while being folded can be obtained. At this time, the anisotropic thermally conductive filler is oriented in the plane direction of the resin sheet 50 .
[0082] Thereafter, the folded-back portion of the resin sheet 50 is cut and removed using a cutter 54 (see FIG. 4B). As a result, a laminate 55 of a plurality of resin sheets 50 that are not connected to one another is obtained.
[0083] Next, a step (f) is performed in which the obtained laminate 55 is sliced in a direction perpendicular to the surface direction of the resin sheet 50 using a cutter 57 (see FIG. 4C). This allows the thermally conductive sheet 1 to be obtained (see FIG. 4D). The thermally conductive sheet 1 can also be manufactured through such steps. EXAMPLES
[0084] Hereinafter, the embodiments of the present invention will be described in more detail with reference to examples, but the embodiments of the present invention are not limited to the following examples.
[0085] The raw materials used in the examples and comparative examples are as follows. (Matrix components) Silicone A: Polydimethylsiloxane with a mass average molecular weight of 140,000 Silicone B: Vinyl-containing compound (MR-53, manufactured by Dow Toray Industries, Inc.) Peroxide: (Dow Toray Co., Ltd., RC-4 50P FD) mixture ·Silane coupling agent: Octyltrimethoxysilane
[0086] (Thermal conductive filler) Carbon fiber A: Mitsubishi Chemical Corporation, K223HM (fibrous, fiber length: 200 μm / fiber diameter: 11 μm) Carbon fiber B: Mitsubishi Chemical Corporation, K23EHM (fibrous, fiber length: 200 μm / fiber diameter: 11 μm) Carbon fiber C: Mitsubishi Chemical Corporation, K223HM (fibrous, fiber length: 50 μm / fiber diameter: 11 μm) Graphite powder: Nippon Graphite Industries Co., Ltd., CPB (flake-like, particle size: 22 μm) Zinc oxide particles: Sakai Chemical Industry Co., Ltd., zinc oxide type 1 (spherical, particle size: 0.8 μm) Alumina particles A: DAW-03 (spherical, particle size: 5 μm), manufactured by Denka Co., Ltd. Alumina particles B: Denka Co., Ltd., ASFP-09S (spherical, particle size: 1 μm) Alumina particles C: AP10 (scale-shaped, particle size: 10 μm) manufactured by DIC Corporation Magnesium hydroxide: Konoshima Chemical Co., Ltd., EP-1A (spherical, particle size: 2 μm)
[0087] Example 1 In this example, the thermally conductive sheet 1 was produced by the second production method. 100 parts by mass of silicone A (polydimethylsiloxane with a mass average molecular weight of 140,000), 117 parts by mass of carbon fiber A, 60 parts by mass of carbon fiber B, 60 parts by mass of graphite powder, 304 parts by mass of zinc oxide particles, and 3.8 parts by mass of a silane coupling agent were kneaded together using two rolls 51, and then sheeted out to produce a resin sheet 50 made of a silicone-based composition having a thickness of approximately 1.0 to 1.2 mm. In this embodiment, the volume fraction of carbon fiber A relative to the entire resin sheet 50 is 20 volume %, the volume fraction of carbon fiber B is 10 volume %, the volume fraction of graphite powder is 10 volume %, the volume fraction of zinc oxide particles is 20 volume %, and the total volume fraction of the thermally conductive filler is 60 volume %.
[0088] Next, the prepared resin sheet 50 is folded and laminated so that the sheets are in close contact with each other (see FIG. 4A). At this time, the carbon fibers A and B and the graphite powder are oriented in the plane direction of the laminated resin sheet 50.
[0089] Next, in the obtained laminate, the folded-back portion of the resin sheet 50 is cut and removed with a cutter 54. This results in a laminate 55 of a plurality of resin sheets 50 that are not connected to one another (see FIG. 4B). Thereafter, the laminate 55 was sliced in a direction perpendicular to the surface direction of the resin sheet 50 (see FIG. 4C) to obtain a thermally conductive sheet 1 having a thickness of 2 mm and in which the carbon fibers and graphite powder were oriented in the thickness direction (see FIG. 4D).
[0090] Example 2 A thermally conductive sheet was completed in the same manner as in Example 1, except that a resin sheet 50 made of a silicone-based composition having a thickness of about 1.0 to 1.2 mm was produced by the following method. 100 parts by mass of silicone A, 118 parts by mass of carbon fiber A, 60 parts by mass of carbon fiber B, 60 parts by mass of graphite powder, 305 parts by mass of zinc oxide particles, 4.0 parts by mass of silane coupling agent, and 16 parts by mass of magnesium hydroxide were kneaded together using two rolls 51 and then sheeted out to produce a resin sheet 50 made of a silicone-based composition having a thickness of approximately 1.0 to 1.2 mm. In this embodiment, the volume fraction of carbon fiber A relative to the entire resin sheet 50 is 20 volume%, the volume fraction of carbon fiber B is 10 volume%, the volume fraction of graphite powder is 10 volume%, the volume fraction of zinc oxide particles is 20 volume%, the volume fraction of magnesium hydroxide is 2.5 volume%, and the total volume fraction of the thermally conductive fillers is 62.5 volume%.
[0091] Example 3 A thermally conductive sheet was completed in the same manner as in Example 1, except that a resin sheet 50 made of a silicone-based composition having a thickness of about 1.0 to 1.2 mm was produced by the following method. 100 parts by mass of silicone A, 202 parts by mass of carbon fiber A, 67 parts by mass of carbon fiber B, 34 parts by mass of graphite powder, 348 parts by mass of zinc oxide particles, and 4.5 parts by mass of silane coupling agent were kneaded using two rolls to produce a resin sheet 50 having a thickness of approximately 1.0 to 1.2 mm. In this embodiment, the volume fraction of carbon fiber A relative to the entire resin sheet 50 is 30 volume%, the volume fraction of carbon fiber B is 10 volume%, the volume fraction of graphite powder is 5 volume%, the volume fraction of zinc oxide particles is 20 volume%, and the total volume fraction of the thermally conductive fillers is 65 volume%.
[0092] Example 4 A thermally conductive sheet was completed in the same manner as in Example 1, except that a resin sheet 50 made of a silicone-based composition having a thickness of about 1.0 to 1.2 mm was produced by the following method. 100 parts by mass of silicone A, 232 parts by mass of carbon fiber A, 34 parts by mass of carbon fiber B, 66 parts by mass of graphite powder, 257 parts by mass of zinc oxide particles, and 3.5 parts by mass of silane coupling agent were kneaded using two rolls to produce a resin sheet 50 having a thickness of approximately 1.0 to 1.2 mm. In this embodiment, the volume fraction of carbon fiber A relative to the entire resin sheet 50 is 35 volume%, the volume fraction of carbon fiber B is 5 volume%, the volume fraction of graphite powder is 10 volume%, the volume fraction of zinc oxide particles is 15 volume%, and the total volume fraction of the thermally conductive fillers is 65 volume%.
[0093] Example 5 A thermally conductive sheet was completed in the same manner as in Example 1, except that a resin sheet 50 made of a silicone-based composition having a thickness of about 1.0 to 1.2 mm was produced by the following method. 100 parts by mass of silicone A, 90 parts by mass of carbon fiber A, 60 parts by mass of carbon fiber B, 60 parts by mass of graphite powder, 380 parts by mass of zinc oxide particles, and 4.5 parts by mass of silane coupling agent were kneaded using two rolls to produce a resin sheet 50 having a thickness of approximately 1.0 to 1.2 mm. In this embodiment, the volume fraction of carbon fiber A relative to the entire resin sheet 50 is 15 volume%, the volume fraction of carbon fiber B is 10 volume%, the volume fraction of graphite powder is 10 volume%, the volume fraction of zinc oxide particles is 25 volume%, and the total volume fraction of the thermally conductive filler is 60 volume%.
[0094] Example 6 A thermally conductive sheet was completed in the same manner as in Example 1, except that a resin sheet 50 made of a silicone-based composition having a thickness of about 1.0 to 1.2 mm was produced by the following method. 100 parts by mass of silicone A, 137 parts by mass of carbon fiber A, 45 parts by mass of carbon fiber B, 142 parts by mass of zinc oxide particles, and 2.0 parts by mass of silane coupling agent were kneaded with two rolls to produce a resin sheet 50 having a thickness of approximately 1.0 to 1.2 mm. In this embodiment, the volume fraction of carbon fiber A in the entire resin sheet 50 is 37.5 volume%, the volume fraction of carbon fiber B is 12.5 volume%, the volume fraction of zinc oxide particles is 15 volume%, and the total volume fraction of the thermally conductive filler is 65 volume%.
[0095] Example 7 A thermally conductive sheet was completed in the same manner as in Example 1, except that a resin sheet 50 made of a silicone-based composition having a thickness of about 1.0 to 1.2 mm was produced by the following method. 100 parts by mass of silicone A, 355 parts by mass of carbon fiber A, 40 parts by mass of graphite powder, 410 parts by mass of zinc oxide particles, and 5.0 parts by mass of a silane coupling agent were kneaded using two rolls 51 and then sheeted out to produce a resin sheet 50 made of a silicone-based composition having a thickness of approximately 1.0 to 1.2 mm. In this embodiment, the volume fraction of carbon fiber A relative to the entire resin sheet 50 is 45 volume%, the volume fraction of graphite powder is 5 volume%, the volume fraction of zinc oxide particles is 20 volume%, and the total volume fraction of the thermally conductive filler is 70 volume%.
[0096] Comparative Example 1 A thermally conductive sheet was completed in the same manner as in Example 1, except that a resin sheet 50 made of a silicone-based composition having a thickness of about 1.0 to 1.2 mm was produced by the following method. 100 parts by mass of silicone A, 135 parts by mass of carbon fiber A, 45 parts by mass of carbon fiber B, 185 parts by mass of zinc oxide particles, and 2.0 parts by mass of silane coupling agent were kneaded with two rolls to produce a resin sheet 50 having a thickness of approximately 1.0 to 1.2 mm. In this embodiment, the volume fraction of carbon fiber A relative to the entire resin sheet 50 is 37.5 volume%, the volume fraction of carbon fiber B is 12.5 volume%, the volume fraction of zinc oxide particles is 20 volume%, and the total volume fraction of the thermally conductive filler is 70 volume%.
[0097] Comparative Example 2 A thermally conductive sheet was completed in the same manner as in Example 1, except that a resin sheet 50 made of a silicone-based composition having a thickness of about 1.0 to 1.2 mm was produced by the following method. 100 parts by mass of silicone A, 335 parts by mass of carbon fiber A, 25 parts by mass of graphite powder, 320 parts by mass of alumina particles A, 105 parts by mass of alumina particles B, and 2.5 parts by mass of silane coupling agent were kneaded using a two-roll mill to produce a resin sheet 50 having a thickness of approximately 1.0 to 1.2 mm. In this embodiment, the volume fraction of carbon fiber A relative to the entire resin sheet 50 is 40 volume%, the volume fraction of graphite powder is 3 volume%, the volume fraction of alumina particles A is 22.5 volume%, the volume fraction of alumina particles B is 7.5 volume%, and the total volume fraction of the thermally conductive fillers is 73 volume%.
[0098] Comparative Example 3 A thermally conductive sheet was completed in the same manner as in Example 1, except that a resin sheet 50 made of a silicone-based composition having a thickness of about 1.0 to 1.2 mm was produced by the following method. 110 parts by mass of silicone A, 87 parts by mass of graphite powder, 190 parts by mass of alumina particles B, and 2.0 parts by mass of a silane coupling agent were kneaded with two rolls to prepare a resin sheet 50 having a thickness of about 1.0 to 1.2 mm. In this embodiment, the volume fraction of the graphite powder relative to the entire resin sheet 50 is 27 volume %, the volume fraction of the alumina particles B is 36 volume %, and the total volume fraction of the thermally conductive filler is 63 volume %.
[0099] Comparative Example 4 A thermally conductive sheet was completed in the same manner as in Example 1, except that a resin sheet 50 made of a silicone-based composition having a thickness of about 1.0 to 1.2 mm was produced by the following method. 100 parts by weight of silicone A, 1.6 parts by weight of silicone B, 0.7 parts by weight of peroxide, 180 parts by weight of carbon fiber C, and 80 parts by weight of alumina particles C were kneaded with two rolls to produce a resin sheet 50 having a thickness of approximately 1.0 to 1.2 mm. In this embodiment, the volume fraction of the carbon fibers C relative to the entire resin sheet 50 is 40 volume %, the volume fraction of the alumina particles C is 10 volume %, and the total volume fraction of the thermally conductive filler is 50 volume %.
[0100] [Evaluation test] (1) Load value at 50% compression The thermally conductive sheets produced in the examples and comparative examples were further cut into disk-shaped evaluation samples having a diameter of 12 mm and a thickness of 2 mm. The measuring device used was an Instron 5969 (manufactured by Instron). The sheet was compressed at a compression speed of 5 mm / min to a thickness of "thickness before measurement x 0.5" (50% compression), and the load value at that time (N / 113 mm 2 The initial load value was measured. The compressed state was then maintained for one minute, and the load value (N / 113 mm 2 The results are shown in Table 1. The ratio of the load value after 1 minute to the initial load value was also calculated. The results are shown in Table 1.
[0101] (2) Thermal resistance at 20% compression The thermally conductive sheets produced in the examples and comparative examples were further cut into evaluation samples having a diameter of 33 mm and a thickness of 2 mm. The measuring device used was a TIMtester1400 (manufactured by AnalysisTech), and the sheet was compressed to a thickness of "thickness before measurement x 0.8" (20% compression), and the thermal resistance was measured in that state. The sample temperature during measurement was 25°C. The results are shown in Table 1.
[0102] (3) Tracking Ability 5A to 5C are diagrams for explaining a method for evaluating tracking ability. The thermally conductive sheets produced in the examples and comparative examples were further cut into evaluation samples 71 each having a length of 40 mm, a width of 40 mm and a thickness of 2 mm. The conformability of the evaluation sample 71 was evaluated by the following method. The results are shown in Table 1. An evaluation sample 71 is placed on a lower glass plate 72. An aluminum plate 75 measuring 10 mm in length, 10 mm in width, and 1 mm in thickness is placed in the center of the upper surface of the evaluation sample 71. Furthermore, an upper glass plate 73 is placed on the aluminum plate 75 (see FIG. 5A). In this state, a downward load is applied to the upper glass plate 73, and the upper glass plate 73 is moved at a speed of 5 mm / min until the gap between the upper surface of the lower glass plate 72 and the lower surface of the upper glass plate 73 becomes 2 mm. This causes the aluminum plate 75 to be pressed into the evaluation sample 71 (see FIGS. 5B and 5C). As a result, a depression 77 is formed along the outer edge of the aluminum plate 75. In this state, for depression 77 generated on the outer edge of aluminum plate 75, a microscope is used to measure the width dimension W (see FIG. 5C) of the opening on each side of aluminum plate 75. Based on the measured values, the followability is evaluated according to the following criteria. FIG. 5C is an enlarged view of the vicinity of region A in FIG. 5B. ◯: The maximum width of the opening was less than 1000 μm. ×: The maximum width of the opening was 1000 μm or more.
[0103] [Table 1]
[0104] The embodiments disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, and it is intended to include all modifications within the meaning and scope of the claims. [Explanation of symbols]
[0105] 1. Thermally conductive sheet (sheet-shaped thermally conductive composition) 2. Matrix Components 4. Thermally conductive filler 4C Carbon Fiber 4G Graphite powder 4Z Zinc oxide powder 11 IC chip 12 Heat sink 30 Extruder 31 Flow Path 32 First Gap 33 Second Gap 34 Screw 40, 50 Resin sheet 51, 52 53 Table 54, 57 Cutter 55 Laminate 71 Evaluation Samples 72 Lower glass plate 73 Upper glass plate 75 Aluminum Plate 77 Depression
Claims
1. A sheet-shaped thermally conductive composition comprising a resin composition containing silicone and a thermally conductive filler, When compressed by 50%, the initial compression load was 1.0 N / mm 2 The ratio of the compressive load value after 1 minute to the initial compressive load value is 0.5 or less, The apparent thermal conductivity when compressed and deformed by 20% is 22.8 W / mK or more. Thermally conductive composition.
2. The compression load value after the one minute elapsed was 0.4 N / mm 2 2. The thermally conductive composition of claim 1, wherein:
3. The thermally conductive composition according to claim 1 or 2, wherein the resin composition contains polydimethylsiloxane as the silicone.
4. The thermally conductive composition according to any one of claims 1 to 3, wherein the resin composition contains, as the thermally conductive filler, an anisotropic thermally conductive filler and a non-anisotropic thermally conductive filler.
5. The thermally conductive composition according to any one of claims 1 to 4, wherein the resin composition contains, as thermally conductive fillers, a fibrous filler, a scaly filler, and a spherical filler.
6. The thermally conductive composition according to any one of claims 1 to 5, wherein the resin composition contains, as a thermally conductive filler, carbon fibers, scaly graphite powder, and spherical zinc oxide particles.
7. 7. The thermally conductive composition according to claim 6, wherein a total content of the carbon fibers, the scaly graphite powder, and the spherical zinc oxide particles in the thermally conductive composition is 50 volume % or more and 70 volume % or less.
8. The thermally conductive composition according to claim 6 or 7, wherein the content of the carbon fiber in the thermally conductive composition is 30 volume % or more and 45 volume % or less.
Citation Information
Patent Citations
Method for manufacturing heat conductive sheet
JP2014031501A
Thermally conductive sheet
WO2019244890A1